Measurable reliability dimensions for Islamic websites - Nassr, Rasheed; Mahmud, Murni; Md Tap, Abu Osman; Aliyu, Mansur (2013)
Studies have shown that many Muslim users question religious websites. This is due to unrestricted cyberspace where anybody can publish any sort of information. This paper investigates the text-based dimensions that may improve reliability of Islamic websites. It is found that reliability of Islamic websites involves the same principles of reliability established in other types of website. However, reliability of Islamic websites is distinguished by permanent referencing to evidence from the Quran and Sunnah, reflecting perceptions of all mazhabs, publishing fatwa, Ijtih